A Computational Analysis of Blood Flow through Portal Vein under Normal and Extrahepatic Obstructions (Journal of Bangladesh Academy of Sciences, 2018)
Portal hypertension is an alarming disease globally whereas Extrahepatic portal vein obstruction (EHPVO) is an important cause of portal hypertension among children in most of the Asian countries. The frequent occurrence of this disease is due to the formation of thrombosis in the portal vein. To acquire insights into the behaviour of hemodynamics, EHPVO case is studied by the technique of computational fluid dynamics (CFD) by considering partial block formation with different sizes inside the main portal vein. On the basis of block sizes, three cases namely normal portal vein (without block in the portal vein) case, 40% block in the portal vein case and 85% block in the portal vein case are simulated by assuming a 2D steady, laminar and fully developed flow with no-slip wall condition using AnsysTM Fluent. Our study reveals that the flow distribution between the left and right branches of the portal vein is significantly influenced by the formation of the block in the main portal vein. It is concluded that Extrahepatic portal vein obstruction leads to the possibility of Hypertrophy and Atrophy complex to the liver and could heighten the risk of liver diseases. Our numerical examination will play a great role to the Liver Specialist for understanding the flow behavior with obstructed flow path as well as the diagnosis of associated liver disease and their treatments.Journal of Bangladesh Academy of Sciences, Vol. 41, No. 2, 183-199, 2017